GENERATIVE METRICS AND SLOVENIAN VERSE (Philological Studies, 2022)
This article discusses the main generative metric theories and the question of their applicability to the analysis of Slovenian verse. The attempt at a generative metric analysis of Slovenian verse is based on Prešeren's and Kette's iambic pentameters, while the paper also presents the findings of statistical verse analyses carried out for the purposes of the thesis of the same title, which complement the already existing findings on the Slovenian iambic pentameters. Particular attention is paid to the problem of ambivalent monosyllables and trisyllables and polysyllables extending over at least two icts. Comparison of hypothetical realisations with those supported by the material shows that the only example of a rare realisation is the realisation of a bold position with an accented syllable of an uninitially accented polysyllable followed by an accented syllable of another only inically accented polysyllable, which was confirmed in the material in only one case.